Gene therapy and kidney diseases - Nadia Tavakolidakhrabadi; Wen Y. Ding; Moin A. Saleem; Gavin I. Welsh; Carl May (Molecular Therapy: Methods & Clinical Development, 2024)
Chronic kidney disease (CKD) poses a significant global health challenge, projected to become one of the leading causes of death by 2040. Current treatments primarily manage complications and slow progression, highlighting the urgent need for personalized therapies targeting the disease-causing genes. Our increased understanding of the underlying genomic changes that lead to kidney diseases coupled with recent successful gene therapies targeting specific kidney cells have turned gene therapy and genome editing into a promising therapeutic approach for treating kidney disease. This review paper reflects on different delivery routes and systems that can be exploited to target specific kidney cells and the ways that gene therapy can be used to improve kidney health.